Synthesis of a hemoglobin-conjugated triblock copolymer for oxygen carrying and specific recognition of cancer cells. Issue 76 (13th October 2017) - Bu, Huixuan; Xu, Xin; Chen, Jiaming; Cui, Yuecheng; Wang, Li-Qun
Abstract : Considering that hypoxia causes resistance to anti-cancer therapeutics, we synthesized a hemoglobin-based nanocarrier for oxygen carrying and recognition of cancer cells. Abstract : Tumour hypoxia, which has a negative effect on most anti-cancer treatments, has caused extensive concern over recent years. Concerned with this issue, this paper reports a hemoglobin-based oxygen nanocarrier (HBOC) functionalized with oxygen carrying and cancer cell recognition ability. First,  the triblock copolymer poly[2-(methacrylamido) glucopyranose]- b -poly(methacrylicacid)- b -poly(butylmethacrylate) (PMAG- b -PMAA- b -PBMA), in which the first block consists of glucose units, was synthesized and characterized. Following the self-assembly of the amphiphilic copolymer into micelles in phosphate buffer solution, hemoglobin was conjugated onto the micelles through a condensation reaction between the carboxyl groups on PMAA and the amino groups on Hb. The HBOC, with a mean diameter of around 147 nm, is stable and disperses homogeneously in phosphate buffer solution. In addition, an in vitro cytotoxicity study revealed that the HBOC is biocompatible. More importantly, this HBOC was demonstrated to hold excellent capacity for oxygen binding. Moreover, cellular uptake indicated that the HBOC was internalized more easily by cancer cells than normal cells, which means that the HBOC shows specific recognition of cancer cells. Therefore, the hemoglobin-conjugated polymer that we prepared could be a promising nanocarrier for tumour therapy.